Residual efficacy of spinosad and spinetoram on traditional and new improved rice varieties on the mortality of Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae). (September 2020) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.
Abstract: Residual effects of insecticides sprayed on grains play a remarkable role in stored product protection. Over decades, the residual impact of many insecticides has been investigated. However, the negative outcomes of those neurotoxic insecticides on the biotic and abiotic environment project the requirement of seeking for alternatives. Spinosad, a bacterial formulation, has been tested for its residual efficacy on different storage and food processing facilities but the effects vary with the commodity type. Moreover, a more recent and related compound spinetoram possesses little information about its residual efficacy on traditional and new improved rice varieties maintained under storage conditions. Therefore, the objective of this research was to determine the residual efficacy of spinosad and spinetoram applied on traditional and new improved rice varieties found in Sri Lanka on the mortality of Rhyzopertha dominica over different durations of storage. Label rate of spinosad, spinetoram or distilled water (diluent/control) was sprayed on traditional/new improved rice varieties followed by kept in storage for 0–5 months. Every month a bioassay was conducted by introducing R. dominica adults to the treated grains. Mortality of R. dominica adults was determined at 3 and 10 days following introduction. In general, the adult mortality at 10 days following introduction was higher than 3 days. At 5 months following spraying, the maximum residual efficacy of spinosad was shown by Kaluheeneti, Red Basmathi, Red Nadu and Suwandel whereas the same effect of spinetoram was observed in Kaluheeneti and Suwandel. Overall, spinetoram demonstrates better residual efficacy than spinosad over 5-month storage period for the rice varieties tested. Highlights: Spinosad and spinetoram were applied on traditional and new improved rice varieties. Residual efficacy of insecticides over five months was tested. Rhyzopertha dominica was used in the bioassay. Spinetoram has higher residual efficacy than spinosad.